New invasive pest, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) attacking corn in Bengkulu, Indonesia - Ginting, Sempurna; Zarkani, Agustin; Wibowo, Risky Hadi; Sipriyadi, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
Spodoptera frugiperda or Fall Armyworm (FAW) is one of the new pests that attack corn plantations in Indonesia. The pest outbreak was reported in America in 2016 and later spread to Africa and Asia, where it was first reported in Thailand in 2018. In March 2019, the first infestation of FAW in Indonesia was reported on corn in Pasaman, West Sumatra province. Losses due to this pest on corn plants in Africa were between 8.3-20.6 million tons per year or valued at 2.481-6.187 million US$/year. This study was aimed to evaluate the damage on of corn plants varieties due to S. frugiperda attacks in Bengkulu Province, Sumatra-Indonesia. The corn varieties involved in this study were Bisi 18, Skada, Paragon, Bima 20 and Nasa 29. The research method was a survey, sampling with a scouting system. The results showed that among the varieties of corn in Bengkulu, Bisi 18, Skada, and Nasa 29 were partially resistant, while the Paragon and Bima 20 varieties were susceptible to the attack of S. frugiperda. Natural enemies found in the cornfields were S. frugiperda multiple nucleopolyhedro virus(SfMNPV), Nomura earileyi, predators Coleomegilla maculata (Coleoptera: Coccinellidae), and parasitoids (Diptera: Tachinidae). It is expected that the results of this study could be used for further research to control S. frugiperda